2005
DOI: 10.1103/physrevlett.95.065502
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Thermal Conductivity of a Single Carbon Nanotube

Abstract: Although the thermal properties of millimeter-sized carbon nanotube mats and packed carbon nanofibers have been readily measured, measurements for a single nanotube are extremely difficult. Here, we report a novel method that can reliably measure the thermal conductivity of a single carbon nanotube using a suspended sample-attached T-type nanosensor. Our experimental results show that the thermal conductivity of a carbon nanotube at room temperature increases as its diameter decreases, and exceeds 2000 W/mK fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
489
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 807 publications
(512 citation statements)
references
References 19 publications
16
489
2
5
Order By: Relevance
“…The thermal conductivity κ of single-wall carbon nanotubes (SWCNTs) and multi-wall carbon nanotubes (MWCNTs) has been studied experimentally. Fujii et al [2] measured κ of individual SWCNT and found κ >2000 W m -1 K -1 for a CNT diameter of 9.8 nm, which further increased with decreasing diameter. Kim et al [3] reported κ >3000 W m -1 K -1 for MWCNT at room temperature while that of SWCNTs and MWCNTs in bundles was ~250 and ~20 W m -1 K -1 respectively [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal conductivity κ of single-wall carbon nanotubes (SWCNTs) and multi-wall carbon nanotubes (MWCNTs) has been studied experimentally. Fujii et al [2] measured κ of individual SWCNT and found κ >2000 W m -1 K -1 for a CNT diameter of 9.8 nm, which further increased with decreasing diameter. Kim et al [3] reported κ >3000 W m -1 K -1 for MWCNT at room temperature while that of SWCNTs and MWCNTs in bundles was ~250 and ~20 W m -1 K -1 respectively [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indeed suggests them to be superior thermal conductors, but the reported thermal conductivity values vary widely between 200 and 3000 W/K·m in the literature. 2,[5][6][7][8][9][10][11][12] This incongruity in some cases can be attributed to variations in thermal contact resistance R c , 13 a parameter that has recently received much attention, with studies on the subject reporting values that vary widely. 13,[14][15][16][17][18][19][20][21][22] For example, Maune et al perform thermometry employing electrical breakdown of CNTs to report R c values of 0.6--3.0 K·m/W, 15 whereas Tsen et al…”
mentioning
confidence: 99%
“…Consideration of the morphology, the diameter of SWCNTs and our present computational resource leads to the decision to define the size of the computational domain to be a cubic cell of 100×100×100 nm 3 . The same FEM in our previous work 19 is used in this paper.…”
Section: Finite Element Calculationmentioning
confidence: 99%
“…1 To make the best of the high thermal conductivity (more than 3000 W/mK) 2,3 of CNTs, the effects of some structure factors of CNTs such as the dispersion, morphology and size on the properties of CNT/epoxy composites have become a hot topic. [4][5][6][7][8][9][10][35][36][37] Yang 11 explored the effect of the dispersion of CNTs on the thermal conductivity of carbon nanotube/epoxy composites (kc) by functionalizing CNTs.…”
Section: Introductionmentioning
confidence: 99%